Doubled haploid production from Spanish onion (Allium cepa L.) germplasm: embryogenesis induction, plant regeneration and chromosome doubling - Fayos, Oreto; Vallés, María P.; Garcés-Claver, Ana; Mallor, Cristina; Castillo, Ana M. (Frontiers in Plant Science, 2015)
The use of doubled haploids in onion breeding is limited due to the low gynogenesis efficiency of this species. Gynogenesis capacity from Spanish germplasm, including the sweet cultivar Fuentes de Ebro, the highly pungent landrace BGHZ1354 and the two Valenciana type commercial varieties Recas and Rita, was evaluated and optimized in this study. The OH-1 population, characterized by a high gynogenesis induction, was used as control. Growing conditions of the donor plants were tested with a one-step protocol and field plants produced a slightly higher percentage of embryogenesis induction than growth chamber plants. A one-step protocol was compared with a two-step protocol for embryogenesis induction. Spanish germplasm produced a 2 to 3 times higher percentage of embryogenesis with the two-step protocol, Recas showing the highest percentage (2.09%) and Fuentes de Ebro the lowest (0.53%). These percentages were significantly lower than those from the OH-1 population, with an average of 15% independently of the protocol used. The effect of different containers on plant regeneration was tested using both protocols. The highest percentage of acclimated plants was obtained with the two-step protocol in combination with Eco2box (70%), whereas the lowest percentage was observed with glass tubes in the two protocols (20-23%). Different amiprofos-methyl (APM) treatments were applied to embryos for chromosome doubling. A similar number of doubled haploid plants were recovered with 25 or 50 µM APM in liquid medium. However, the application of 25 µM in solid medium for 24 h produced the highest number of doubled haploid plants. Somatic regeneration from flower buds of haploid and mixoploid plants proved to be a successful approach for chromosome doubling, since diploid plants were obtained from the 4 regenerated lines. In this study, doubled haploid plants were produced from the four Spanish cultivars, however further improvements are needed to increase their gynogenesis efficie